The Influence of Family Structure on Adolescent Academic Achievement : A Comparative Analysis - Ingrid Hovland; Solveig Sether (International Journal of Humanities and Social Sciences Reviews, 2024)
This study examines the effects of family structure on adolescent academic achievement, focusing on nuclear, single-parent, and extended family settings. Drawing on data from diverse cultural backgrounds, the research investigates how parental involvement, socioeconomic status, and family support impact academic outcomes. The findings reveal that family support plays a pivotal role in academic success across all family structures, with adolescents in stable and supportive environments achieving better academic results.